2018
DOI: 10.24084/repqj16.284
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Source Location in the Distribution Grid Using Time-Synchronized Measurements

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Taking into account the aforementioned, Babaev et al [12] demonstrated the challenge of employing just a few cycles of rms values (magnitudes only) for impedance calculation, as these values have to be chosen from certain strict realizations of data. A considerable improvement is to perform a continuous assessment of the impedance over the range of frequencies by utilizing a large amount of data samples.…”
Section: Estimation Algorithmmentioning
confidence: 99%
“…Taking into account the aforementioned, Babaev et al [12] demonstrated the challenge of employing just a few cycles of rms values (magnitudes only) for impedance calculation, as these values have to be chosen from certain strict realizations of data. A considerable improvement is to perform a continuous assessment of the impedance over the range of frequencies by utilizing a large amount of data samples.…”
Section: Estimation Algorithmmentioning
confidence: 99%
“…2. In this measurement, a Fluke 438-II instrument is used, which is a class A type measuring instrument [20]. The used measurement instrument follows EC 61000-4-30 Class A, where the measurements are aggregated over a period of 3 seconds.…”
Section: Introductionmentioning
confidence: 99%